2006
DOI: 10.1007/s00294-005-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative mitochondrial RNA polymerase from Physarum polycephalum: characterization, expression, purification, and transcription in vitro

Abstract: Mitochondrial RNA polymerases (mtRNAPs) are necessary for the biogenesis of mitochondria and for proper mitochondrial function since they transcribe genes on mtDNA for tRNAs, rRNAs, and mRNAs. The unique type of RNA editing identified in mitochondria of Physarum polycephalum is thought to be closely associated with transcription, and as such, RNA editing activity would be expected to be closely associated with the mtRNAP. In order to better characterize the role of mtRNAPs in mitochondrial biogenesis and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Sequences encoding such an enzyme have been specifically amplified from many protists (Cermakian et al 1996;Li et al 2001) and can typically be found in sequenced protist nuclear genomes. The corresponding activity has been experimentally verified in some lineages (Grams et al 2002;Miller et al 2006). However, as noted above, the mitochondrial genomes of R. americana and other jakobids encode a bacterial-type RNA polymerase (Gray et al 2004).…”
Section: Mitochondrial Gene Expression and Controlmentioning
confidence: 87%
“…Sequences encoding such an enzyme have been specifically amplified from many protists (Cermakian et al 1996;Li et al 2001) and can typically be found in sequenced protist nuclear genomes. The corresponding activity has been experimentally verified in some lineages (Grams et al 2002;Miller et al 2006). However, as noted above, the mitochondrial genomes of R. americana and other jakobids encode a bacterial-type RNA polymerase (Gray et al 2004).…”
Section: Mitochondrial Gene Expression and Controlmentioning
confidence: 87%
“…Overall core structures are well conserved, even between single and multi-subunit polymerases. Although there are currently no equivalent structures for the mitochondrial RNA polymerase from Physarum polycephalum (Pp mtRNAP), based on its high degree of homology with the bacteriophage T7 RNA polymerase (T7 RNAP) (Miller et al 2006;Gott and Rhee 2007), the basic features of the Pp mtRNAP elongation complex are likely to be similar. Of particular interest to our findings here is that in the T7 RNAP elongation complex, sequences immediately upstream of the point of nucleotide addition are involved in the 7-8-bp RNA:DNA hybrid and the z9-nt transcriptional bubble, while roughly 8 bp of downstream DNA lies against a positively charged patch on the exterior of the polymerase (Tahirov et al 2002;Steitz 2002, 2004;Temiakov et al 2004).…”
Section: Editing In the Context Of Transcription Elongationmentioning
confidence: 99%
“…Recently, the P. polycephalum mitochondrial RNA polymerase has been cloned (Miller et al 2006), and it has been found to add non-DNA-templated nucleotides to the 39 end of RNAs (Miller and Miller 2008). Using chimeric templates and in vitro mitochondrial transcription elongation complexes Rhee et al (2009) demonstrated the importance of 9 base pairs (bp) to either side of C insertion sites in directing this type of editing event.…”
Section: Introductionmentioning
confidence: 99%